Differential timing of mitochondrial activation in rat dorsal striatum induced by procedural learning and swimming - Pegueros-Maldonado, Rogelio; Fuentes-Ibañez, Antonio; Monroy, Mónica M.; Gutiérrez, Oscar A.; Serafín, Norma; Pech-Pool, Santiago M.; Díaz-Muñoz, Mauricio; Quirarte, Gina L. (Frontiers in Molecular Neuroscience, 2024)
Stressful experiences form stronger memories due to enhanced neural plasticity mechanisms linked to glucocorticoid hormones (cortisol in humans, corticosterone in rats). Among other neural structures, the dorsal striatum plays a role in the corticosterone-induced consolidation of stressful memories, particularly in the cued water maze task. Neural plasticity is related to mitochondrial activity due to the relevance of energy production and signaling mechanisms for functional and morphological neuronal adaptations. Corticosterone has been shown to enhance brain mitochondrial activity by activating glucocorticoid receptors. In this context, striatum functions are susceptible to change in relation to mitochondrial responses. Based on this evidence, we hypothesized that training in the cued water maze would induce an increase in corticosterone levels and mitochondrial activity (mitochondrial membrane potential and calcium content) in the dorsal striatum, and that these adaptations might be related to memory consolidation of the task. We used an ELISA assay to evaluate plasma and striatal corticosterone levels; mitochondrial activity was determined with the florescent probes MitoTracker Red (mitochondrial membrane potential) and Rhod-2 (calcium content) in brain slices containing the dorsal striatum of rats trained in the cued water maze and euthanized at different times after training (0.5, 1.5, or 6.0 h). We also analyzed the effect of post-training inhibition of striatal mitochondrial activity by OXPHOS complex 1 inhibitor rotenone, on the consolidation of the cued water maze task. We found that cued water maze training induced an increase in corticosterone levels and a time-dependent elevation of mitochondrial membrane potential and mitochondrial calcium content in the dorsal striatum. Unexpectedly, rotenone administration facilitated the retention test. Altogether, our results suggest that enhanced mitochondrial activity in the dorsal striatum is relevant for cued water maze consolidation. The increase in mitochondrial activity was contextually associated with an elevation of corticosterone in plasma and the dorsal striatum. Additionally, our swimming groups also showed an increase in mitochondrial activity in the dorsal striatum, but with a different pattern, which could suggest a differential functional adaptation in this structure.